Development of anthropometry database for Malaysian university student - Saravanan Perianan (Universiti Malaysia Perlis, 2008)
Anthropometry defined as a measurement of the human body and its biomechanical characteristic. Database defined as an organized collection of related records. The purpose of this project is to develop a Database System for designer. A database system has been created using Microsoft Access as data storing and Visual Basic as the output. This study aimed at providing a proper database system on University Student ranged from 18 till 25 years old. The subjects, 50 male and 50 female we randomly selected to group according to their stature in 5th and 95th percentile, mean in other word is 50th percentile and Standard Deviation Value. A set of 26 dimensions was measured and recorded on each individual. It is also frequently assumed that anthropometric dimensions are normally distributed. The result shows that this system is being very easy to handle by anyone.